Uma análise estratégica da gestão pública da Prefeitura Municipal de Salvador: um estudo da área de assistência social no ano de 2006 - Santos, Reinaldo Saback (2009)
To present dissertation this intends to analyze the strategy of the public administration of the Municipal City hall of Salvador, starting from the actions developed in the area of social attendance in the year of 2006. For so much, necessary she made to understand the development of the strategy concept and of strategic planning in the extent of the municipal public administration; to analyze the strategic focus used by the SEDES to combat the poverty in the city of Salvador; to identify the developed strategic actions, through the projects and programs of social attendance, implanted by the SEDES, More social and Cidade Mãe Fundation the year of 2006 in the Municipal district of Salvador; and to identify the innovations implemented in the projects with the purpose of evaluating the reach of the social transformations undertaken the lacking community of the city of Salvador close to. The methodology adopted for the development of the research understood the interview structured with subjects opened the manager of the SEDES close to, as well as with the managers of the Most social and of the Cidade Mãe Fundation. It is ended that the social subject has been one of the impediments in the municipal public administration, mainly, because of the exacerbated poverty and even the lack of resources, that they are not enough to institute and to maintain the projects in the area of social development. Face to the exposed, the study shows that the strategy of performance of the municipal public power-Municipal City hall of Salvador, through to SEDES, that this has if given through the strategic performance and partner with the Most social and the Cidade Mãe Fundation determined a new administration pattern in the area of social attendance